Self-Directed Oral Vitamin D Supplementation in Professional Ballet Dancers: A Randomized Controlled Trial Pilot Study. Issue 3 (September 2019) - Rowan, Fiachra E.; Benjamin-Laing, Harry; Kennedy, Aedín; De Medici, Akbar; Beasley, Ian; Haddad, Fares S.
Inadequate levels of vitamin D may lead to poor performance in professional dancers. Therefore, dietary supplementation may be essential in this population. This longitudinal pilot study to a randomized controlled trial assessed dancer compliance with self-directed oral vitamin D supplementation. Seventy-one dancers, 41 females and 30 males with a mean age of 31.1 years, were recruited from The Royal Ballet, London. Baseline serum 25(OH)D levels were measured and dancers were interviewed, examined, and provided with oral supplements for the winter period, November 2011 to March 2012. Dancers with normal serum 25(OH)D levels were provided with maintenance supplements (1, 000 IU/day) and those with insufficient or deficient serum 25(OH)D levels were given a loading dose of 60, 000 IU weekly for 2 and 6 weeks, respectively. Serum 25(OH) D levels were measured at 1 and 2 years and dancers were sampled for compliance with instructions. Mean compliance during loading and maintenance was 86% and 50%, respectively. Mean serum 25(OH)D levels at start and end of the study period were 79.3 ±31.6 nmol/L and 78.68 ± 19.8 nmol/L, respectively. Only one-third of dancers with insufficient (N = 5) and deficient (N = 5) serum vitamin D levels improved to normal values. It is concluded that professional ballet dancers demonstrate good compliance with self-directed loading doses of vitamin D supplementation but poor compliance with maintenance doses. Poor maintenance compliance may have accounted for the low rates of serum vitamin D level improvement among dancers with insufficient or deficient levels.